Microwave Assisted Cationic Polymerization of Different Type Palm Oils with Boron Trifluoride Ethereal Catalyst - Muhamad Farid; Bambang Soegijono; Zainal Alim Mas’ud (Indonesian Journal of Chemistry, 2019)
Indonesia is a major producer of palm oils. However, more than 76% of the production is exported as crude palm oil (CPO) with low economic values. Chemical conversion is necessary to produce more valuable derivatives of renewable biobased material including a thermoplastic polymer. In this study, crude palm oils (CPO), refined-bleached deodorized palm oil (RBDPO) and refined bleached deodorized palm oil olein (RBDPOO) were converted under microwave-assisted cationic polymerization with the boron trifluoride ethereal catalyst. The precursors were irradiated using the commercial microwave with various reaction conditions. The raw material compositions, iodine values, and functional groups of the raw material and polymers were analyzed by gas chromatography, titrimetry, and Fourier Transform infrared spectrophotometry, respectively. The differential scanning calorimetric (DSC) was used to observe the thermal characteristics of the polymers. The iodine value of the resulting polymer products was lower than the raw materials which indicated the decrease of the C=C bonds due to the polymerization. This result is supported by the decreased intensity of alkene bands in the infrared spectra of the product. The DSC thermogram curve proved that the product is a thermoplastic polymer with a melting point ranged from 40.3 to 45.2 °C; and the freezing point of 22.5 to 28.1 °C. In conclusion, palm oil-based thermoplastic polymer was successfully synthesized and characterized, and the best result was achieved when using RBDPOO as starting material.